Strategi Pengembangan Hutan Kemasyarakatan Dalam Program Perhutanan Sosial Di Kawasan Hutan Lindung Gunung Lembean Wilayah Kesatuan Pengelolaan Hutan Unit V - Hombokau, Immanuel Carter Aldo; Tasirin, Johny S.; Walangitan, Hengki D. (AGRI-SOSIOEKONOMI, 2023)
The study aims to analyze the potential of biophysical civil-forest clearances, analyze economic, institutional, social and cultural conditions, and track stakeholders in determining civil-forest development strategies in the region of Lembean Mountain Reserves. The study was conducted for three months, ranging from March to May 2023. The data used is primary and secondary data. Primary data is collected through interviews, based on questionnaires. The number of respondents to the weight of four respondents with both expert and experienced levels of people's empowerment around the forest region. The number of respondents to give a twenty-first rate to those of a forest-farm group with a permit to use a community forest. The data collected in primary data concern economic conditions, institutional, social and cultural conditions, and stakeholder in determining development strategies. The turnaround strategy is a research strategy developed for the development of community forests in the Lembean Mountain Forest Area. The strategy is to facilitate the establishment and strengthening of group institutions, facilitate businesses wishing to invest with community groups through mutually beneficial cooperation, and develop patterns of agroforestry systems that have products and economic value.